GalNAc in vaginal secretions: a potential non-invasive risk indicator associated with the risk of premature rupture of membranes - Lu Wang; Yan Chen; Jiale Chen; Jie Zhou; Zhen Jia; Yu Chen (PLoS ONE, 2025)
Premature rupture of membranes (PROM) is a major contributor to preterm birth and neonatal morbidity. Current diagnostics are predominantly reactive and detect rupture only after it occurs. In a clinical cohort of 60 pregnant women (20 with PROM, 40 gestational controls at 31–36 weeks), we developed and validated a colorimetric assay for N-acetyl-D-galactosamine (GalNAc) in vaginal secretions. GalNAc levels were significantly lower in the PROM group than in controls, and the assay exhibited linearity, precision, stability, and resistance to interference. Receiver-operating characteristic analysis yielded an AUC of 0.821 (95% CI 0.80–0.97). These data support reduced vaginal GalNAc as a potential non-invasive risk indicator of PROM. While longitudinal validation is required, this approach may enable early risk stratification to guide preventive interventions.